PENGARUH ORIENTASI PASAR TERHADAP INOVASI PRODUK PADAUKM SMESCO - Djamaris, Aurino RA; Anitawati, Maria Th (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
As a business center in Jakarta, SME TOWER provides modern and complete facilities so it is expected to become one stop shopping area for local and international consumers who want to buy KUKM Indonesia products. SME TOWER serves as place for meeting, event, exhibition, conference, shopping or to know the development of international market. This research was conducted to find out the influence of market orientation (customer orientation, competitor orientation, and inter-functional orientation) towards product innovation of Small and Medium Enterprises (SMEs) . Data obtained from small and medium enterprises that use SMECO facilities focusing on handicraft and fashion products.  The sample with purposive sampling was chosen after coordination with LLP-KUKM SMESCO as the parent of the business incorporated in the UKM Gallery to request the willingness of the related businesses to become respondents., 56 were obtained as samples in this study, but only 30 filled the research questionnaire.  Data was analyzed using descriptive quantitative, and multiple linear regression. Primary data obtained through survey method with questionnaire instrument as a tool. The result indicates that customer orientation and competitor orientation have significant influence to product innovation while inter-function orientation has no influence on product innovation. Customer orientation, competitor orientation, and inter-functional orientation together have a significant effect on product innovation. The competitor's orientation has the most powerful influence on product innovation.